Perceptions of Time-Use in Rural Tanzanian Villages: Working With Gender-Sensitive Tools in Nutritional Education Meetings - Schlindwein, Izabela Liz; Bonatti, Michelle; Bundala, Nyamizi Hashim; Naser, Kim; Löhr, Katharina; Hoffmann, Harry Konrad; Sieber, Stefan; Rybak, Constance (Frontiers in Sustainable Food Systems, 2020)
Food consumption and nourishment are related to the availability and use of resources by different social groups within a country. Communities experience hunger not just due to biophysical restrictions, but also their socio-cultural conditions. For this reason, international scientific cooperation seeking to improve nourishment must be interdisciplinary and connected to disciplines covering all relevant dimensions, including hunger, health and well-being, gender, and inter-ethnic relations. Studies on constraints and drivers of food consumption in Sub-Saharan Africa indicate that although women make decisions regarding the type of meals consumed, they lack control over food production, especially on small farms. While the term gender equally is commonly found in discourses on nourishment projects, knowledge regarding gender programs and education for men in remote patriarchal villages in Eastern Africa is rare. To close this research gap, this study seeks to understand (1) basic notions of masculinities and femininities of this inter-ethnic group; and (2) how traditional knowledge can influence decisions related to Unpaid Care Work and nourishment. The case study area is inhabited by the Wagogo, a predominantly pastoralist and patrilineal tribe practicing settled agriculture or migrating to urban areas throughout Tanzania. To achieve these research goals, we explicitly develop pedagogical strategies to interact with adults living in the villages, separated into men and women. These pedagogical tools encompass Nutritional Education involving 80 participants, including female and male farmers, community leaders, primary school teachers, and health professionals. Based in time-use field of knowledge and proposed activities based on participatory methods, we established bonds of trust with the community, initiating a truly open dialogue about food consumption and decision-making. This study reinforces the need to address the ethnic identities of the researched regions in order to not just comprehend the traditions and culture, but also the food and nutrition of the indigenous people.